A generating functional approach to the sd-model with strong correlations - Izyumov, Yu.A.; Chaschin, N.I.; Alexeev, D.S. (Condensed Matter Physics, 2005)
A Kadanoff-Baym-type generating functional approach, earlier developed by the authors to strongly correlated systems, is applied to the sd-model with strong sd-coupling. Formalism of the Hubbard X -operators was used, and equation for electron Green’s function was derived with functional derivatives over external fluctuating fields. Iterations in this equation generate a perturbation theory near the atomic limit. Hartree-Fock type approximation is developed within the framework of this theory, and the problem of a metal–insulator phase transition in sd-model is discussed.